The making it guide to crafting - Creators of Making It (New York, New York) (2020)
"With the all-star duo of Amy Poehler and Nick Offerman leading the way with puns, advice, and good vibes, Making It became the competition series we didn't know we needed, stealing our hearts and encouraging our most creative ideas. Tapping into that success, this well-rounded crafting guide will offer in-depth looks at some of the best DIY crafts that were featured on the show and inspired by the Makers themselves. Introductions to woodworking, fiber arts, paper crafts, and more enable readers to experiment and customize their own creations at home. And the projects are accessible to all skill levels, so you can get just as crafty as the Makers did. Drawing on the show's hilarity, creativity, and overall positivity, this crafting guide will inspire and energize you to DIY whatever you put your mind to-it'll be like having Nick and Amy right there with you"--